2007
DOI: 10.1177/000312240707200307
|View full text |Cite
|
Sign up to set email alerts
|

Climbing the Dispute Pagoda: Grievances and Appeals to the Official Justice System in Rural China

Abstract: In the wake of heightened scholarly and media attention to the growing volume of conflict in rural China, this article represents the first effort to use survey data to identify the causes both of popular grievances and of popular actions taken to resolve them in the Chinese countryside. An analysis of data collected in 2002 from almost 3,000 households across six provinces shows that the volume and character of grievances, as well as the volume of appeals to the official justice system, exhibited substantial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
83
2
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(92 citation statements)
references
References 59 publications
4
83
2
3
Order By: Relevance
“…Collected histories of many disputes reveal a pyramid-shaped distribution of action, with only some experiences escalating from one level to the next, progressively narrowing as it reaches the top, typically defined as court proceedings (Miller & Sarat 1980Murayama 2007, pp. 29-30;Nielson & Nelson 2005b; but see Michelson 2007aMichelson , 2008. The pyramid shape graphically depicts an empirical generalization that holds in most studied complex societies: Relatively few grievances are taken to lawyers, courts, or officials, and most never make it to trial.…”
Section: Behavioral Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Collected histories of many disputes reveal a pyramid-shaped distribution of action, with only some experiences escalating from one level to the next, progressively narrowing as it reaches the top, typically defined as court proceedings (Miller & Sarat 1980Murayama 2007, pp. 29-30;Nielson & Nelson 2005b; but see Michelson 2007aMichelson , 2008. The pyramid shape graphically depicts an empirical generalization that holds in most studied complex societies: Relatively few grievances are taken to lawyers, courts, or officials, and most never make it to trial.…”
Section: Behavioral Approachesmentioning
confidence: 99%
“…Researchers conceptualize decisions about how to handle problems as reflecting a calculus that balances resources, costs, stakes, and the expected returns of different courses of action. Costs, potential returns, and decision points are usually defined with reference to law, and the resources scholars consider are frequently those that would facilitate law's use (but see Michelson 2007a), such as money to pay for attorneys, court fees, or bribes to officials, knowledge about law and legal institutions, and connections to legally sophisticated or politically influential parties (e.g., Carlin et al 1966;Lochner 1975;Michelson 2007aMichelson , 2008. Costs and the stakes at risk are typically limited to money, but some scholars also consider social costs in the form of disrupted relationships, hostility, or lost goodwill (e.g., Silberman 1985, Michelson 2008.…”
Section: Social Class and Socioeconomic Inequalitymentioning
confidence: 99%
“…However, none of the differences she describes suggests that there are strong relationships between demographic variables and experiencing problems, and many of the differences she describes seem quite logical; it is not surprising that those with higher incomes experience more significant consumer problems because their incomes allow them to make more significant purchases of consumer goods, which in turn increases their exposure to potential problems with major consumer purchases. Michelson (2007) conducted a survey in several areas of rural China (six provinces), and examined what factors might account for grievance experience. He found that grievances were most prevalent in economically distressed areas.…”
Section: The Incidence Of Grievancesmentioning
confidence: 99%
“…Again, with one notable exception, while specific relationships are uncovered here and there (e.g., those with a prior dispute experience or who have previously used a lawyer may be more likely to claim for some types of problems), no clear pattern is evident in the various studies. The notable exception is Michelson's finding in his study conducted in 37 villages across six provinces of China that families with strong political connections were more likely to pursue grievances than were families without such connections (Michelson 2007). 23 As noted above, few studies have sought to examine the potential role of psychological variables on claiming behavior, and what has been done does not show strong relationships.…”
mentioning
confidence: 99%
“…Firstly, rurality creates natural barriers for rural residents in limiting the availability of public services including legal ones (Fu, 2003;Michelson, 2007aMichelson, , 2008Liu, 2011). The problem is structural and improvement in delivery through information technology has had only limited impact.…”
mentioning
confidence: 99%